2014
DOI: 10.1136/jfprhc-2013-100730
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use among women presenting to pharmacies for emergency contraception: an opportunity for intervention

Abstract: Objectives Most women who use emergency contraception (EC) do so because of unprotected sexual intercourse or condom failure and so remain at risk of pregnancy unless they commence an effective method of contraception. In Great Britain, increasingly women now choose to obtain EC from a pharmacy; however, pharmacists do not currently provide effective ongoing contraception. We sought to determine the views of women obtaining EC from pharmacies and clinicians working in sexual and reproductive health care (SRH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Some GPs did not see extended pharmacy services as a priority for them (Wilcock & Harding, ), were not convinced that these services reduced their workload (Atkins et al., ; Latif et al., ; Porteous & Bond, ) and preferred services to be simplified (Porteous & Bond, ; Wilcock & Harding, ). Even when GPs were supportive of community pharmacy services (Blenkinsopp, Tann, Evans, & Grime, ; Michie, Cameron, Glasier, & Greed, ; Morecroft et al., ; Wilcock & Harding, ), this was associated with suggestions that they supervised and authorised pharmacists’ activities (Blenkinsopp et al., ; Bradley et al., ; Maddox, Halsall, Hall, & Tully, ; Michie et al., ).
I guess we need to educate them, but I don't feel that's my responsibility…we're going to have to chase it up and make sure they are doing it properly. (GP, Bradley et al., )
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some GPs did not see extended pharmacy services as a priority for them (Wilcock & Harding, ), were not convinced that these services reduced their workload (Atkins et al., ; Latif et al., ; Porteous & Bond, ) and preferred services to be simplified (Porteous & Bond, ; Wilcock & Harding, ). Even when GPs were supportive of community pharmacy services (Blenkinsopp, Tann, Evans, & Grime, ; Michie, Cameron, Glasier, & Greed, ; Morecroft et al., ; Wilcock & Harding, ), this was associated with suggestions that they supervised and authorised pharmacists’ activities (Blenkinsopp et al., ; Bradley et al., ; Maddox, Halsall, Hall, & Tully, ; Michie et al., ).
I guess we need to educate them, but I don't feel that's my responsibility…we're going to have to chase it up and make sure they are doing it properly. (GP, Bradley et al., )
…”
Section: Resultsmentioning
confidence: 99%
“…Even when GPs were supportive of community pharmacy services (Blenkinsopp, Tann, Evans, & Grime, 2008;Michie, Cameron, Glasier, & Greed, 2014;Morecroft et al, 2015;Wilcock & Harding, 2007), this was associated with suggestions that they supervised and authorised pharmacists' activities (Blenkinsopp et al, 2008;Bradley et al, 2012;Maddox, Halsall, Hall, & Tully, 2016;Michie et al, 2014).…”
Section: Perceived Value Of Services/rolesmentioning
confidence: 99%
“…A study of nearly 500 contraception providers in the United States showed almost three-quarters supported pharmacists initiating combined hormonal contraception (CHC), progestogen-only pills (POPs) and injectable contraception (IC),18 and a UK study of SRH clinicians showed that >90% felt positively about pharmacists initiating POP at the time of EC 19…”
Section: Introductionmentioning
confidence: 99%
“…Of course, women are increasingly choosing to access EC from the pharmacy (in countries where this is available without prescription), but most pharmacists cannot provide ongoing hormonal contraception without a prescription. In a survey of women attending UK pharmacies for EC, 64% indicated that they would value the opportunity to receive a supply of contraception from the pharmacy . A pilot study showed that women provided with a 1‐month supply of a progestogen‐only pill along with EC from a pharmacy were more likely to be using effective contraception 2 months later than women attending pharmacies where they only received advice on where to obtain supplies of contraception (56% versus 16%).…”
Section: Contraception After Ecmentioning
confidence: 99%
“…In a survey of women attending UK pharmacies for EC, 64% indicated that they would value the opportunity to receive a supply of contraception from the pharmacy. 76 A pilot study showed that women provided with a 1-month supply of a progestogen-only pill along with EC from a pharmacy were more likely to be using effective contraception 2 months later than women attending pharmacies where they only received advice on where to obtain supplies of contraception (56% versus 16%). Larger robust studies are needed to determine if this strategy can increase the uptake of effective contraception after EC from the pharmacy.…”
Section: Do Women Want To Start Effective Contraception After Ec?mentioning
confidence: 99%